Technology development for semi-arid sub-Saharan Africa: Theory, performance and constraints - Sanders, H.S.; Ramaswamy, S.; Shapiro, Barry I. (IAEA, 1997)
The paper proposes a theory of technology Development for semi-arid regions. It then evalautes the theory by reviewing the characteristics of technologies successfully introduced into the regions and, with modeling, identifying some constraints to further technology introduction of the type proposed. Some specific policy recommendations to accelarate technology introduction are recommended.